THE SAPE STRAIT CEPHALOPOD RESOURCE AND ITS RESPONSE TO CLIMATE VARIABILITY - Abdul Ghofar (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Of seven cephalopod species occurring in the Sape Strait, four species of squid constitute 90% of the annual cephalopod catches. The squid fishery is described, with emphasis on its fluctuating catches due to the combined effects of fishing and climate variability. Two most important fishing gears, ‘bagan perahu’ and ‘jala oras’ were used and standardized in catch and fishing effort analysis. The southern oscillation index (SOI) was used to represent the climate variability component.A model was then developed by means of incorporating the SOI, fishing effort and squid catch. Average annual values of these three components were used to construct the model. The model can be a useful tool for predicting the squid catches. Its use for forecasting and managing the fishery requires regular monitoring the catch, fishing effort and the SOI, preferably monthly. Research and management implications of this finding are discussed.